2006
DOI: 10.1111/j.1526-4610.2006.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Topiramate and Sodium Valporate in Migraine Prevention: A Randomized Blinded Crossover Study

Abstract: This study demonstrates that treatment with topiramate and sodium valporate both significantly reduce migraine headache. This effect of topiramate and sodium valporate has previously been shown to reduce migraine headache, and we postulate that treatment with topiramate and sodium valporate may have a similar benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 25 publications
6
47
1
1
Order By: Relevance
“…Two additional Class I studies report topiramate is as effective as propranolol 16 or sodium valproate, 17 drugs previously established as effective for migraine prevention. In the first study, subjects given topiramate 50 mg/day had reduced mean migraine frequency (episodes/month) from baseline (6.07 Ϯ In a crossover Class I trial (2-month washout between therapies) comparing topiramate 50 mg/day with sodium valproate 400 mg/day, both groups showed improvement from baseline in headache frequency, intensity, and duration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional Class I studies report topiramate is as effective as propranolol 16 or sodium valproate, 17 drugs previously established as effective for migraine prevention. In the first study, subjects given topiramate 50 mg/day had reduced mean migraine frequency (episodes/month) from baseline (6.07 Ϯ In a crossover Class I trial (2-month washout between therapies) comparing topiramate 50 mg/day with sodium valproate 400 mg/day, both groups showed improvement from baseline in headache frequency, intensity, and duration.…”
mentioning
confidence: 99%
“…In the first study, subjects given topiramate 50 mg/day had reduced mean migraine frequency (episodes/month) from baseline (6.07 Ϯ In a crossover Class I trial (2-month washout between therapies) comparing topiramate 50 mg/day with sodium valproate 400 mg/day, both groups showed improvement from baseline in headache frequency, intensity, and duration. 17 Average monthly migraine frequency decreased by 1.8 times with sodium valproate (baseline 5.4 Ϯ 2.5; posttreatment 3.6 Ϯ 2.1; CI 1.0 -2.6; p Ͻ 0.001), as compared with a 3-time reduction with topiramate (baseline 5.4 Ϯ 2.0; posttreatment 2.4 Ϯ 2.4; CI 2.1-3.9; p Ͻ 0.001). Headache intensity decreased by 3.7 with sodium valproate (baseline 7.7 Ϯ 1.2; treatment 4.0 Ϯ 2.1; CI 2.9 -4.6; p Ͻ 0.001), as compared with a reduction of 3.6 with topiramate (baseline 6.9 Ϯ 1.2, treatment phase 3.3 Ϯ 1.5; CI 2.9 -4.3; p Ͻ 0.001).…”
mentioning
confidence: 99%
“…Other studies have shown that TPM at 100 mg/day is effective in prevention of migraine headache, and in reducing the severity of the attack. [28][29][30] Results of electrophysiological evaluation by P300 show no statistical differences either at the first or at the third month. At the first month, latencies were increased in frontal (from 320-326) and central (from 307-322) areas but these increases did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with this view, several agonists at GABA receptors have been used as prophylactic antimigraine drugs. In this context, valproate (Cutrer et al 1997a;Shaygannejad et al 2006), baclofen in a small open study (Hering-Hanit 1999), and gabapentin (Di Trapani et al 2000) may prevent migraine attacks, while valproate has also been suggested to be effective in the acute treatment of migraine in another small open trial (Mathew et al 2000). Despite the above clinical evidence, it should be kept in mind that not all of the aforementioned compounds are selective in their action at GABA receptors, and the mechanisms involved in their antimigraine effect remain unclear.…”
Section: Gaba Receptorsmentioning
confidence: 99%